Effect of the slurry composition on the piezoelectric properties of PZT ceramics fabricated via materials extrusion 3D printing. Issue 12 (15th June 2023) - Liu, Kai; Xia, Yuhang; Zhang, Qingqing; Du, Yanying; Shi, Yusheng; Joshi, Sanjay; Yan, Chunze; Wu, Yanjiao; Huang, Shangyu; Sun, Huajun
Abstract: Herein, the effect of the binder content in lead zirconate titanate (PZT) slurry has been systematically studied to improve the piezoelectric properties of PZT ceramics prepared via material extrusion 3D printing. For smooth printing, a slurry with a binder concentration ranging from 6 to 12 wt% was proposed. The porosity of the green body first decreased and then increased with an increase in the binder concentration, and the minimum porosity was obtained when the binder concentration reached 10 wt%. Samples with increased density were obtained after debinding and lead-rich atmosphere sintering. PZT piezoceramics fabricated using a binder content of 10 wt% exhibit the maximum relative density (96.9%), largest piezoelectric constant (342.6 pC/N) and dielectric constant (1621). Based on the above process, the wood pile structure and helical twentytetrahedral structural components were successfully fabricated using the material extrusion process. This research lays the foundation for the engineering application of 3D printing to fabricate high-performance piezoceramics with complex shapes.